ARCHITECTURAL-URBAN-MODELING OF THE NETWORK OF PUBLIC SPACES IN THE CENTRAL PART OF THE LARGEST CITY (ON THE EXAMPLE OF KHARKIV): Array - Dreval, I.; Zhabina, A. (Municipal economy of cities (Technical science), 2021)
The paper is dedicated to the problem of creating a network of public spaces in the downtown area of a major city as an effective means of its humanization. The goal of the work is to justify and develop a graphical model of the network of public spaces in the structure of the downtown area of a major city on example of Kharkiv. Analysis of the scientific works of foreign and domestic authors has shown that the issues relating to the formation of a spatially integrated network of public spaces have not been subjected to special scientific scrutiny. The use of the law of isomorphism of structures of urban planning systems suggested that a network of public spaces could have a linear-nodal spatial organization. It is shown that open public spaces are located along the streets and should be seen as part of the city’s communication framework. The placement of a significant variety of small public service elements on the first floors of the city center neighborhood development contributes to the formation of public spaces along the streets. These pedestrian spaces providing connections to subway stations are “linear” components of the network. The presence of open, undeveloped spaces in areas close to the entrances to subway stations creates attractive conditions for the formation of new types of public spaces. On the basis of analysis of placement of 8 subway stations in the structure of the downtown area of Kharkiv there was justified the assumption that it is their areas that are considered to be “nodal” elements of the networks of public spaces. In this way, a spatially integrated network of public spaces is created and presents an effective means of humanizing the urban environment as a whole. The study of the architectural and urban construction of the network of public spaces in the city structure led to the conclusion of the effectiveness of such a measure in social, economic and aesthetic aspects.